Invasive methods for detection of Helicobacter pylori infection in gastric disorders patients undergoing endoscopy from Mosul city, Iraq - Muhammad Abdul-Ghani Muhammad; Anmar Ahmed Altaie; Bassima Ahmed Abdullah (Romanian Journal of Infectious Diseases)
Objectives. The identification of H. pylori in Iraq lacks a standardized technique and there is limited information on the efficacy of different diagnostic methods. This research aims to determine the prevalence of H. pylori and evaluate the effectiveness of invasive techniques, namely the Rapid Urease Test (RUT), histopathological examination, and ure A gene by PCR, for detecting H. pylori. Method. Gastric biopsies specimens were collected from 50 patients with gastric disorders who underwent endoscopy after meeting the inclusion criteria. Patients were classified into H. pylori-positive cases and negative cases by testing positive with at least two of the three testing methods, according to the case definition used in the study. Outcomes. Of the 50 gastric biopsies, 58% were H. pylori-positive cases, 26% were H. pylori -negative cases, and the last 16% were indeterminate case according to cases definition. The ure A gene PCR was the most sensitive method, followed by histopathological examination and RUT testing, with sensitivities of 96.6%, 86.2% and 79.3% respectively. Histopathology examination was the most specific with a specificity of 95.2%, followed by ure A gene PCR with 85.7%, while RUT was the least specific with a specificity of 81%. Conclusion. The current study revealed a moderate prevalence of H. pylori infection compared with previous studies. The sensitivity and specificity of the three invasive methods varied, and a combination of two methods may be necessary for a definitive diagnosis of H. pylori infection.